Tentacular Thinking: Towards an Alternative Epistemology of Relationality - Oikonomou, Andreas (Homo Virtualis, 2025)
This article introduces and analyzes the concept of tentacular thinking as a radically alternative epistemological, ethical, and aesthetic proposition. Grounded in process philosophy, ecofeminism, posthumanist theory, and science and technology studies (STS), tentacular thinking proposes a non-linear, networked, and interdependent approach to understanding the world. The study traces its historical roots, emphasizing the contributions of Heraclitus, Spinoza, Merleau-Ponty’s phenomenology, and Deleuze and Guattari’s rhizomatic theory. Drawing on examples from biology (mycorrhizal networks, cuttlefish, coral reefs), the article highlights the importance of organic interdependence and relational ontologies. Practical applications are suggested for pedagogy (transdisciplinary curricula, collective learning trajectories), art (participatory works, open installations), and politics (community assemblies, care-based workshops). Furthermore, the article offers a critical examination of certain posthumanist narratives that remain technocentric and subtly anthropocentric, emphasizing instead the need for embodied, ecological, and material entanglements. Tentacular thinking emerges not merely as a theoretical framework but as a practical proposal for reweaving our connection with the world. The study concludes by advocating for the gradual cultivation of a new ethics of kinship, care, and participatory co-creation. Within this framework, uncertainty, complexity, and interdependence are transformed into creative resources, outlining a new path toward collective coexistence and planetary belonging.